Dynamic platelet adhesion in patients with an acute coronary syndrome: The effect of antiplatelet therapy. (16th November 2016) - Tsoumani, Maria E.; Tatsidou, Prokopia T.; Ntalas, Ioannis V.; Goudevenos, John A.; Tselepis, Alexandros D.
Abstract: Platelet adhesion and aggregation are key functions leading to thrombus formation. The effect of aspirin, clopidogrel, and ticagrelor on platelet aggregation has been well established, however, there is limited data on the effect of these drugs on platelet adhesion. We therefore evaluated the effect of these drugs on platelet adhesion in acute coronary syndrome (ACS) patients. Citrated blood was collected from 50 ACS patients loaded with 325 mg of aspirin (baseline) and at 5 days after the administration of aspirin 100 mg/day and clopidogrel (600 mg loading dose, 75 mg/day) ( n = 26) or ticagrelor (180 mg loading dose, 90 mg × 2/day) ( n = 24). High on-treatment platelet reactivity (HTPR) to clopidogrel was estimated by vasodilator stimulated phosphoprotein (VASP) phosphorylation assay. Platelet adhesion to collagen was studied for 6 min under high shear stress and was evaluated using the time to platelet recruitment (TPR), the perimeter and average area of each adherent object, number of adherent objects, and the total percent of surface coverage (SC%). Six ACS patients exhibited HTPR to clopidogrel and excluded from the platelet adhesion assays. TPR and SC% values were similar among patient groups at baseline and controls. However, all other adhesion parameters were different in ACS patients, indicating the formation of more aggregates in regard to controls. At 5 days post-treatment with either clopidogrel or ticagrelor, the TPR values were increased and the SC% values were reduced to a similar extent compared with baseline. However, significant differences were observed in the ticagrelor group in the perimeter, number of adherent objects, and the average area of each adherent object indicating a more potent inhibition of adherence-induced platelet aggregation than clopidogrel. In conclusion, aspirin does not affect platelet adherence to collagen, whereas clopidogrel and ticagrelor inhibit to a similar extent dynamic platelet adhesion at 5 days post-treatment in ACS patients. However, ticagrelor exhibits a greater inhibitory effect on reducing adhesion-induced platelet aggregation.